2016
DOI: 10.1109/tuffc.2016.2589270
|View full text |Cite
|
Sign up to set email alerts
|

Relative Elastic Modulus Imaging Using Sector Ultrasound Data for Abdominal Applications: An Evaluation of Strategies and Feasibility

Abstract: We reconstruct the elastic modulus distribution for one tissue mimicking (TM) phantom and two in vivo biopsy-confirmed liver tumors using curvilinear ultrasound echo data. Spatial distribution of the relative elastic modulus values is determined by solving an inverse problem within a region of interest (ROI). This inverse problem solution requires knowledge of the ultrasonically-measured displacement field in a uniform rectilinear grid to ensure that the resolution on the resultant relative elastic modulus ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…Particularly, results in Table 3 suggested that SSI offers the highest elastic contrast values as compared to SE and ARFI. This observation is consistent with the tissue -mimicking phantom results reported by Palmeri and Nightingale (Palmeri and Nightingale, 2011) and Peng et al (Peng et al , 2016). In the future, viscoelastic tissue properties will be included in this virtual elastography platform.…”
Section: Discussionsupporting
confidence: 93%
“…Particularly, results in Table 3 suggested that SSI offers the highest elastic contrast values as compared to SE and ARFI. This observation is consistent with the tissue -mimicking phantom results reported by Palmeri and Nightingale (Palmeri and Nightingale, 2011) and Peng et al (Peng et al , 2016). In the future, viscoelastic tissue properties will be included in this virtual elastography platform.…”
Section: Discussionsupporting
confidence: 93%
“…If the first and last displacement vectors of the diamond stencil are different and the correlation value of the displacement vector at the center of the stencil is 0.75 or higher, then that center of the stencil is marked as a trusted seed. These seeds are then used in a modified predictive search strategy described in (Peng et al 2016). Initialized seeds from the regularized search and all displacements estimated with correlation coefficients less than 0.4 are then discarded.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to displacement vector tracking and estimation, an important step for all these methods is the approach used to transform displacement data from a sector format to a rectilinear grid. Trigonometric identities using both x and y displacement vectors were used (Peng et al 2016) to generate axial and lateral displacement vectors for the sector array data. An additional post-displacement task was to localize a rectangular region of interest containing the ablated tumor region and regions of normal liver surrounding it from all the displacement tracking methods for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…However, the research on classification recognition algorithm is not mature, and the application of its research results in the actual production line cannot achieve the desired effect. With the development of computer technology [4,5], domestic studies on the detection and classification of foreign matter inspection in pharmaceutical liquids have also made some achievements. Xiao et al [6] mainly carried out studies on detection and tracking of moving foreign matter in ampoule bottle solutions.…”
Section: Introductionmentioning
confidence: 99%